"To be HIV positive is not the end of the world": Resilience among perinatally infected HIV positive adolescents in Johannesburg. (November 2016) - Woollett, Nataly; Cluver, Lucie; Hatcher, Abigail M.; Brahmbhatt, Heena
Abstract: Background: Resilience, or positive adaptation to challenging situations, has potential to improve health outcomes for high risk populations. Resilience may be particularly important for perinatally infected HIV positive adolescents, who are exposed to significant stigma, risks and stressors. Despite recognition that HIV positive adolescents show remarkable resilience in the face of adversity, little is known about how resilience occurs within this population. Methods: The aim of this study was to identify elements of resilience in a group of perinatally infected HIV positive adolescents attending HIV clinics. In-depth interviews were conducted with 25 purposively selected HIV positive adolescents (15 female, 10 male) between the ages of 13–19 years in Johannesburg. Data were analysed in NVIVO 10 using a thematic approach to coding. Results: Despite marked stressors in the lives of these adolescents, a high degree of resilience was described. Characteristics of resilience in this group included a pertinent set of beliefs, including a belief in fate and recognition of personal strength as a consequence of managing adversity. Character traits such as a pragmatic acceptance about one's life, actively taking responsibility, and a robust self-esteem were evident. Social behaviours included the ability to pursue and access adults and healthcare to meet developmental needs, having a desire to support and help others and challenging HIV related stigma. These characteristics were underscored by the capacity for self-reflection. Conclusion: Perinatally infected adolescents, who face high levels of hardship and change, nevertheless exhibit strong resiliency beliefs, traits, and behaviours. Healthcare environments have the potential to be utilized as powerful resources in fostering resilience in HIV positive adolescents, if characteristics of adolescent resilience were integrated into current prevention and intervention programming. Resilience promotion could lead to improved health outcomes for HIV positive adolescents. Highlights: Resilience (or positive adaptation to challenging situations) is evident in perinatally infected adolescents Characteristics of resilience included recognition of personal strength as a consequence of managing adversity A pragmatic acceptance about one's life, actively taking responsibility, and a robust self-esteem were evident. The ability to access adults and healthcare to meet developmental needs, and challenging HIV related stigma was present Health systems are well placed to facilitate characteristics of resilience, impacting patients positively